Socio-economic Condition of Guhele Chhopnarayan Community Forest on Rural Livelihood of Bhojpur Municipality-3, Gupteshwor, Dawan - Rai, Saran Kumar (Intellectual Inception: A Multidisciplinary Research Journal of Bhojpur Campus, 2023)
This paper examines the relationship of community forest with livelihood of rural people. Basically, social, economic and management aspects of the community forest have been discussed in this study. This article is based on primary and secondary data and it follows descriptive research design and quantitative approach. There is two-way relationship between community forest and livelihood of rural people that has been sustained for long time. Rural people apply different techniques to grow forest products and they also use forest products for the fulfillment of their needs. The user groups of this forest have been taken some direct advantages from forest products and also benefitted socially and economically through various forest management activities. Rural people mainly depend on the community forest for firewood, animal fodders and timber products that supports their livelihood. This article focuses on how the well management of community forest is taking place according to the national policy.